Qualitative research & evaluation methods integrating theory and practice : the definitive text of qualitative inquiry frameworks and options - Patton, Michael Quinn (SAGE Publications, Inc., 2015)
The book that has been a resource and training tool for countless researchers and students has been completely revised in its Fourth Edition with hundreds of new examples and stories illuminating all aspects of qualitative inquiry and now offers more balance between applied research and evaluation